Analisis Pengelolaan Media Sosial @Eventbyindonesia Di Visi Agia Global - Ambarini, Nabila Ayu; Bachtiar, Willy; Latif, Alfa Tahufan (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ANALYSIS OF SOCIAL MEDIA MANAGEMENT OF @EVENTBYINDONESIA AT VISI AGIA GLOBALThe rapid growth of social media has encouraged many brands and organizations to utilize digital platforms as strategic tools for information dissemination and brand building. One of them is the Instagram account @eventbyindonesia, managed by Visi Agia Global (VAG), which focuses on providing information about events, festivals, and creative activities across various cities in Indonesia. This study aims to describe the management process of the account using the SOME Model (Share, Optimize, Manage, Engage) as the analytical framework. This research employs a descriptive qualitative approach through observation, in-depth interviews, active participation during the internship period, and documentation analysis. The findings show that in the Share stage, the account has successfully built basic interaction through engaging captions and the use of seven content pillars. However, the dominance of static poster-based content limits the shareability and emotional appeal of the posts. In the Optimize stage, the team monitors trending topics, analyzes audience insights with the help of Hootsuite, and adjusts communication styles, although open two-way conversations remain limited. The Manage stage becomes the most consistently implemented aspect, reflected through regular monitoring, quick responses, and real-time interactions such as reposts and live event coverage through Instagram Stories. In the Engage stage, the account has collaborated with event organizers and several influencers, which has proven effective in increasing reach and engagement, although such collaborations are still not frequentOverall, the management of @eventbyindonesia has been effective in disseminating event information and building public awareness. Nevertheless, further improvements are needed in strengthening two-way interactions, diversifying content formats, and expanding collaboration strategies to enhance sustainable engagement.